Clustering or interacting for knowledge?: Towards an entangled view of knowledge in regional growth policy. Issue 2 (13th June 2016) - Eklinder-Frick, Jens Ola
Abstract : Purpose: – The European Union has an ambition to become the world's most competitive and knowledge-based economy, which entails investments in cluster initiatives. Most researchers, however find that such investments have had limited impact. The notion of creating industrial clusters is influenced by the discourse within new economic geography in which research interests are geared toward facilitating knowledge exchange between industry, university and government. In order to understand how knowledge is created and enacted within a cluster initiative the purpose of this paper is to investigate the interactions between actors participating in a specific innovation process. Design/methodology/approach: – The studied cluster initiative is one of the 55 clusters designated as demonstrating highly sophisticated cluster management by European Union officials, making it an interesting case study for knowledge creation in such environments. The case study entails semi-structured in-depth interviews of 24 respondents. Findings: – The cluster approach encourages a "disentangled" view of knowledge where knowledge is seen as universal and cognitive and therefore possible to disentangle from the context in which it was initially produced. However, my findings suggest that in practice knowledge is "entangled" in the specific context in which it is enacted and produced. Originality/value: – Thus, in practice knowledge is a contextually limited and practical activity that is being enacted when heterogeneous resources interact in producer-user interfaces. This mismatch between strategy and outcome may subsequently help to explain the limited impact of policy on regional growth.